UTILIZATION OF SODIUM ALGINATE AS A FIBER BINDING MEDIUM IN TEXTILE WASTE RECYCLING PROCESS - Zefanya Maria Soraya; Apika Nurani Sulistyati (Runtas: Jurnal Fesyen dan Wastra Nusantara, 2025)
The textile industry plays a vital role in human life but also ranks among the highest contributors to global environmental pollution. Textile waste is often non-biodegradable, leading to severe environmental issues such as water contamination and increased greenhouse gas emissions. One promising solution lies in eco-friendly recycling methods using biomaterials. This study explores the use of sodium alginate, a brown algae-derived biopolymer, as a fiber-binding medium in the recycling of textile waste through a crosslinking method with calcium chloride (CaCl₂). Sodium alginate, which dissolves easily in water, reacts with calcium ions to form a strong and elastic gel. In this process, textile waste in the form of fabric and yarn is broken down into staple fibers and then recombined using sodium alginate and calcium chloride. The crosslinking mechanism strengthens fiber bonds and produces a new alginate-based yarn material suitable for sustainable textile development. Results indicate that this combination forms a water-resistant, flexible, and environmentally friendly binder. Therefore, this method offers an innovative alternative for managing textile waste while promoting circular economy principles in the fashion industry.